Experimental investigation of the vortex-induced vibration of a steep-wave dynamic submarine cable - Hongjun Zhu; Kairui Deng; Zijing Ding; Yue Gao (Ocean Engineering, 2026)

Deep Immunophenotyping Unravels the Double Negative T cells and PD-1-Mediated Inflammatory Exhaustion in Ankylosing Spondylitis - Lu Bai; Jian Gao; Yunyun Xu; Yuexin Yu; Jing Liu; Mathias Hochgerner; Hejian Zou; Xingdong Chen; Feng Qian; Hongjun He; Jiucun Wang (Phenomics, 2026)
Ankylosing spondylitis (AS) is a chronic, immune-mediated inflammatory disorder primarily affecting the axial skeleton. It is characterized by bony fusion and syndesmophyte formation of the spine, leading to compromised mobility, reduced quality of life and increased mortality. However, the underlying immune dysregulation in AS remains poorly understood. We comprehensively profiled the peripheral immune landscape of 30 patients with active AS, all of whom were TNF-α blocker-naïve, capturing the immune profile during the active disease phase without biologic interference. Using advanced 11-color flow cytometry and FlowSOM clustering, 584 immunophenotypes were analyzed in AS and 30 age-and sex-matched healthy controls, with emphasis on both cellular composition and functional characteristics. AS patients displayed a distinctive functional “activated-exhausted” immune phenotype, dominated by CD4 + CD28 + CD38 + PD-1 + T cells and HLA-DR + CD38 + CD4 − CD8 − double-negative (DN) T cells. DN T cells were significantly enriched in HLA-B27-positive patients, suggesting potential as a biomarker. Network analysis revealed seven central immune subsets associated with active disease, while functional assessment demonstrated impaired CD95 + CD8 + T cell apoptosis and disrupted B-cell maturation. These findings provide a detailed functional immune map of biologic-naïve active AS, offering novel mechanistic insights and identifying candidate biomarkers for precision intervention.

Dynamic response of a submerged floating tunnel under coupled wave−current−vehicle loads - Hongjun Zhu; Xu Zhang; Wanhai Xu; Yue Gao; Xiaodong Shen (Ocean Engineering, 2026)

Form-dependent chloroform adsorption behavior from powdered to sintered carbon - Qing Gao; Zhilong He; Jianjun Cheng; Jingwen Li; Dapeng Zhou; Jiahua Shi; Xiuli Chen; Hongjun Liu (Journal of Environmental Chemical Engineering, 2026)

Soil organic carbon and pH govern the divergent trajectories of organic and inorganic sulfur under long-term fertilization - Haotian Shi; Miao Lei; Shaomin Huang; Hongjun Gao; Lu Zhang; Dongchu Li; Shulan Zhang; Xianlu Yue; Qingxu Ma; Wenju Zhang (Journal of Cleaner Production, 2026)

Wake flow structure and hydrodynamic characteristics of flow around a cylinder-plate configuration - Yue Gao; Yuanbo Wang; Tao Tang; Hongjun Zhu; Jiawen Zhong; Tongming Zhou (Ocean Engineering, 2026)

Niche-specific and stage-dependent dynamics of microbial assemblages in the macroalgal cultivation system - Zhizhuo Shao; Xin Gao; Yi Sun; Yunlei Zhang; Hongjun Li (Regional Studies in Marine Science, 2026)

A fidelity-preserved organic geochemical study of the Cambrian and Ordovician black shales in the Tarim Basin, Northwest China - Huajian Wang; Jiaquan Zhou; Yunfeng Yang; Bo Yang; Shuang Gao; Hongjun Wu; Yingjie Yang; Chi Zhang; Yiran Lu; Wenyang Wang; Wang Zhang (International Journal of Coal Geology, 2026)

Mineral-associated organic carbon promotes phosphorus accumulation in a long-term fertilized black soil - Naiyu ZHANG; Xiuzhi ZHANG; Yanhua CHEN; Lehlogonolo Abner MATELELE; Ping ZHU; Hongfang LIU; Xianmei ZHANG; Hongjun GAO; Gu FENG; Chang PENG; Shuxiang ZHANG (Pedosphere, 2026)

Rapid selection of early-maturing and low-ear position maize hybrids suitable for China using genomic prediction - Ping Luo; Wenzhe Li; Lin Zhang; Jie Yang; Houwen Wang; Fei Wang; Ruisi Yang; Xinlong Xu; Ke Yang; Hongjun Yong; Mingshun Li; Jianfeng Weng; et al. (Plant Molecular Biology, 2026)

Performance enhancement evaluation of coal gangue aggregates based on chemical solution modification: mechanical properties and microstructural characteristics - Meng Gao; Hongjun Jing; Jun Dai; Shaojie Chen; Chaowei Zhang; Junwei Shan; Hengfei Zhang; Yuanquan Cui; Shixuan Lei (Chemical Engineering Journal, 2026)

Spatiotemporal patterns of super-emitting diesel vehicles: A scalable remote sensing framework for urban emission hotspot mitigation - Junxia Gao; Yan Liu; Ning Yang; Zeping Cao; Jing Zhao; Lin Wu; Wentian Xu; Binfeng Yan; Zhengyu Jia; Hongjun Mao (Atmospheric Pollution Research, 2026)

Modelling of vortex-induced vibration of a flexible riser in uniform and sheared oscillatory flows using wake oscillators - Shuo Gao; Xu Zhang; Enhao Wang; Menglan Duan; Hongjun Zhu; Wanhai Xu; Qing Xiao; Atilla Incecik (Ocean Engineering, 2026)

Experimental evaluation of the vortex-induced vibration suppression of catenary flexible riser with helical strakes - Hongjun Zhu; Bin Luo; Hongtao Hao; Yue Gao; Tongming Zhou (Ocean Engineering, 2026)

Unraveling synergistic CO2 binding in anion-pillared materials and amine-modified MOFs for direct air capture (DAC) via combined DFT-D3 calculation and PALS experiment - Niu Liu; Dongfang Guo; Shiwang Gao; Hanming Liu; Hongwei Niu; Lianbo Liu; Shiqing Wang; Qi Wang; Huanjun Wang; Wei Xu; Hongjun Zhang (Chemical Engineering Journal, 2026)

Lacticaseibacillus paracasei subsp. paracasei Q- 1 Exhibits Good Safety and Effectively Prevents Escherichia coli K99-Induced Diarrhea in Mice - Fengjie Wang; Li Chen; Yang Li; Guangping Gao; Yanan Wang; Ruili Shi; Hongjun Zhang; Yingyu Chen; Rui Cao; Qiumei Shi; Tonglei Wu (Probiotics and Antimicrobial Proteins, 2026)

Latitude-dependent diversity and assembly processes of coastal microbial communities across multiple trophic levels in the China Seas - Yunlei Zhang; Xin Gao; Zhizhuo Shao; Yi Sun; Zheng Zhang; Hongjun Li; Jinqing Ye (Frontiers in Marine Science, 2025)
Coastal sediment ecosystems function as dynamic interfaces for land-sea interactions, harboring highly complex microbial communities which support vital ecological functions. However, the mechanisms governing microbial diversity maintenance and cross-trophic community assembly at large spatial scales remain poorly explored. In this study, a high-throughput sequencing approach was employed to analyze the bacterial, fungal and protistan communities in surface sediments of the China Seas. As indicated by higher values across most indices, bacterial communities generally exhibited greater richness and alpha diversity compared to fungal and protistan communities. Beta diversity decomposition revealed that species turnover dominated community variations across all three trophic levels, with the highest contribution in bacteria. The neutral community model revealed that stochastic processes exerted a stronger influence on bacterial assembly relative to fungi and protists. Moreover, null model analyses demonstrated that bacterial communities were primarily structured by dispersal limitation, fungal communities by ecological drift, while protistan communities co-regulated by homogeneous selection and homogenizing dispersal. Furthermore, similar latitude-dependent patterns in the α- and β- diversity were observed in bacteria and protists, yet such patterns were distinct for fungi. Finally, based on the correlations between community variations with their assembly mechanisms, regional species pools exerted the strongest influence on bacterial β-diversity, whereas local assembly processes dominated fungal β-diversity. The present study elucidates the trophic-level-dependent assembly rules of coastal microbiomes, thereby establishing a mechanistic foundation for predicting ecosystem responses to global change and informing evidence-based conservation of coastal ecosystems.

Coupled internal/external flow-induced vibration and pipe-seabed impact for hydrogen-mixed submarine pipe span - Hongjun Zhu; Hao Hu; Tang Tang; Yue Gao; Tongming Zhou (Ocean Engineering, 2025)

Experimental investigation of the hydrodynamic response of a cantilevered gas-conveying flexible tube - Hongjun Zhu; Peng Liu; Yue Gao; Lin Ding; Tongming Zhou (Ocean Engineering, 2025)

Characterizations of air pollutants at roadside monitoring stations and traffic emission effects: A case study in Tianjin, China - Fangyuan Zheng; Junxia Gao; Lin Wu; Naixiu Sun; Wentian Xu; Qijun Zhang; Hongjun Mao; Jianfei Peng; Liwei Li; Ning Yang; Bin Liu (Journal of Environmental Sciences, 2025)

Competitive effects and environmental factors driving heavy metal leaching in stabilized municipal solid waste incineration fly ash under extreme conditions - Ze Zhang; Yang Yu; Yi Rao; Ying Wang; Chunjiang Yu; Zhongli Luo; Hongjun Zhao; Xiaona Wang; Ming Gao; Chuanfu Wu; Shu Liu (Journal of Hazardous Materials, 2025)

Multi-perspective analysis of long-term vehicle emissions under intensive policy updates in China - Wentian Xu; Fangyuan Zheng; Zhouzhi Li; Junxia Gao; Hui Tong; Haomiao Niu; Bin Sun; Zhaoyang Fan; Lin Wu; Hongjun Mao (Transportation Research Part D: Transport and Environment, 2025)

Heat stroke-induced central nervous system injury: Mechanisms and therapeutic perspectives - Wenjun Yang; Zhen Gao; Chengjin Wang; Min Wang; Yuan Cao; Yun Li; Shaoqing Shi; Yiqi Wu; Lu Wang; Hongjun Kang (Journal of Thermal Biology, 2025)

Chelation treatment for heavy metals in municipal solid waste incineration fly ash: 300-Day study on stability and environmental risk - Ze Zhang; Yang Yu; Yi Rao; Ying Wang; Chunjiang Yu; Zhongli Luo; Hongjun Zhao; Xiaona Wang; Ming Gao; Qunhui Wang; Chuanfu Wu (Waste Management, 2025)

Long-term effects of cropping regimes on soil organic carbon and aggregate stability in a Mollisol of Northeast China - Cuilan LI; Zhiyuan CAO; Mo ZHU; Hongjun GAO; Xiuzhi ZHANG; Ping ZHU; Jinjing ZHANG (Pedosphere, 2025)

High Yield of Prodigiosin by Serratia marcescens Ka3 Using Additive Huangshui, a Byproduct of Chinese Liquor (Baijiu) - Chuan Wang; Zhongxing Gao; Rui Han; Yaomei Tian; Hongjun Fan; Yuliang Zhang (Current Microbiology, 2025)

FePS3-Nanosheets-Integrated multifunctional nanocomposite hydrogel for multimodal synergistic osteosarcoma therapy and enhanced bone regeneration - Bing Ye; Xirui Jing; Yanlin Su; Wenzhe Sun; Qing Gao; Lian Zeng; Hongwei Lu; Shuo Tang; Yizhou Wan; Tingfang Sun; Zekang Xiong; Xiao Lv; et al. (Chemical Engineering Journal, 2025)

High-Probability Ground Motion Simulation in Maduo County for the Maduo MS7.4 Earthquake in 2021: A Possible Supershear Earthquake - Zongchao Li; Zhiwei Ji; Jize Sun; Hiroe Miyake; Yanna Zhao; Hongjun Si; Mengtan Gao; Yi Ding (Journal of Earth Science, 2025)

Integrated ecological quality assessment of the sea area adjacent to the Yellow River estuary under multiple pollutants - Wen Li; Jinqing Ye; Xin Gao; Yunlei Zhang; Ying Li; Hongjun Li (Frontiers in Marine Science, 2025)
Estuaries are increasingly threatened by pollutants derived from human activities, which severely impair their water quality, biodiversity, and ecological functions. Therefore, within this context, it is essential to conduct comprehensive and scientifically rigorous assessments of estuarine ecological quality. Taking the Yellow River estuary as a case study, a composite index was here developed to evaluate the impacts of eutrophication and heavy metal pollution on estuarine ecological quality. The Trix eutrophication index and potential ecological risk index revealed significant risks of eutrophication and heavy metal pollution. Redundancy analysis identified that nutrients (NO 2 -N and NO 3 -N) and heavy metals (Cd, Hg, and Cr) were the primary pollutants affecting the composition of dominant macrofauna. Threshold Indicator Taxa Analysis was used to identify indicator species for these pollutants and, based on them, bioindicators capable of reflecting eutrophication and heavy metal pollution levels were then determined. A composite index integrating these bioindicators with other biotic indexes was constructed for comprehensive ecological quality assessment. The results showed that the ecological quality of the estuary was good, with values being even lower in the nearshore area. Structural equation modeling confirmed that estuarine ecological quality was significantly influenced, both directly and indirectly, by multiple pollutants, validating the effectiveness of the composite index as an analytical tool. We argue that integrating bioindicators of major pollutants with other benthic indexes into the developed composite index allows to effectively assess the effects of multiple pollutants on estuarine ecological quality and provide valuable insights for ecosystem management.

Corrigendum to ‘Exploring the maximum nitrite production rate through the granular sludge-type reactor to match the needs of anammox process realizing efficient nitrogen removal’ [Environ. Res. 255 (2024) 119158] - Hongjun Zhao; Yan Guo; Xiaona Wang; Haishu Sun; Ming Gao; Chuanfu Wu; Shuang Li; Yu-you Li; Qunhui Wang (Environmental Research, 2025)

Optimization scheduling of household integrated energy systems for improving thermal comfort with low cost - Yunlong Wang; Lu Han; Xinlong Deng; Hongjun Gao (Energy and Buildings, 2025)

Impact of flow velocity on growth performance, muscle texture, and nutritional composition in seabass (Lateolabrax maculatus) - Fan Fei; Yingying Fang; Zhiwen Zhu; Xinyu Liu; Ao Li; Jiawen Zhang; Xiaoqiang Gao; Wenyang Li; Hongjun Yang; Wensheng Li; Chuanxin Zhang; Baoliang Liu (Aquaculture International, 2025)

Effect of Photoperiod on Nutritional Quality of Muscle and Lipid Metabolism of Litopenaeus vannamei - Yingying Fang; Fan Fei; Fulu Guo; Chengliang Zhu; Xiaoqiang Gao; Wenyang Li; Hongjun Yang; Yan Sun; Chuanxin Zhang; Baoliang Liu (Fishes, 2024)
Photoperiod serves as a significant environmental signal for organisms and plays a critical role in regulating their metabolic processes. This research aimed to investigate the lipid metabolism and nutritional quality of adults Litopenaeus vannamei (wet weight: 11.27 ± 0.73 g, body length: 12.45 ± 0.42 cm) under five photoperiods (0L:24D, 8L:16D, 12L:12D, 16L:8D, and 24L:0D) for 40 days in recirculating water systems (RASs). The 24L:0D group increased lipid metabolism, as indicated by increased lipid metabolism enzyme levels and related gene expression linked to lipogenesis. Additionally, shrimp in the 24L:0D exhibited the highest value of crude fat. The 0L:24D showed a significantly reduced content of crude fat compared with the 8L:16D and 12L:12D. In 24L:0D, the content of total essential amino acids (TEAAs), total hydrolyzed essential amino acids (THEAAs), and total non-essential amino acids (TNEAAs) increased significantly. Similarly, the content of polyunsaturated fatty acids (PUFAs) in 24L:0D was also higher than in other groups. Conversely, 0L:24D resulted in lower metabolic activity and a reduction in PUFA content. In conclusion, prolonging light could benefit shrimp cultivation. This study thoroughly examined the effects of varying photoperiods on muscle quality and lipid metabolism in L. vannamei, providing essential insights for the improvement of indoor aquaculture environments. Provision of light for 24 h improves production but has some adverse effects on animal welfare, so a 16 h light cycle is recommended.

Fractal research on pores in oil and gas reservoirs - Inspirations from over 700 high pressure mercury injection experiments - Xingxing Kong; Hongjun Fan; Tingen Fan; Yufei Gao; Haifeng Wang; Pengfei Mu; Dianshi Xiao (Marine and Petroleum Geology, 2024)

Response of soil gross nitrogen mineralization to fertilization practices in China's uplands - Jun Wang; Yinghua Duan; Guanmo Li; Lu Zhang; Dejin Li; Kailou Liu; Xi'an Cui; Boku Zhou; Hongjun Gao; Xiaori Han; Junyong Ma; Shutang Liu; et al. (Journal of Cleaner Production, 2024)

A negative-carbon planning method for agricultural rural industrial park integrated energy system considering biomass energy and modern agricultural facilities - Dewei Jiang; Hongjun Gao; Shuaijia He; Yuan Huang; Junyong Liu (Journal of Cleaner Production, 2024)

Divergent chemical compositions of soil organic matter size fractions under long-term amendments across a climate gradient - Fanbo Song; Ning Hu; Yilai Lou; Huimin Zhang; Ping Zhu; Dongchu Li; Hongjun Gao; Shuiqing Zhang; Yidong Wang (Soil and Tillage Research, 2024)

Whole-process analysis and implementation of a self-powered wireless health monitoring system for railway bridges: Theory, simulation and experiment - Weiqiang Sheng; Hongjun Xiang; Linglong Gao; Jianjun Wang; Junrui Liang; Zhiwei Zhang (Engineering Structures, 2024)

Visualizing of engineered five-helix bundle protein for blocking SARS-CoV-2 variants in live animals - Jianzhong Xian; Zhijun Li; Hongbin Huang; Lei Bi; Zhifeng Guan; Guolong Huang; Min Yang; Zhizeng Gao; Jijin Yao; Zhongzhen Su; Hongjun Jin (Chemical Engineering Journal, 2024)

Emission characteristic, spatial distribution, and health risk of polycyclic aromatic compounds (PAHs, NPAHs, and OPAHs) from light-duty gasoline and diesel vehicles based on on-road measurements - Jiaqi Fu; Tiange Fang; Yutong Gao; Ting Wang; Zhenyu Jia; Dongping Guo; Hongjun Mao (Science of The Total Environment, 2024)

Surface plasmon enhancement of 1D Ag nanowires modified electro-treated BiVO4 photoanode with abundant oxygen vacancies for solar water oxidation - Song Zhang; Hongjun Zhang; Yuan Gu; Xinjie Mao; Xiaoying Gao; Dongbo Xu (Fuel, 2024)

Exploring the maximum nitrite production rate through the granular sludge-type reactor to match the needs of anammox process realizing efficient nitrogen removal - Hongjun Zhao; Yan Guo; Xiaona Wang; Haishu Sun; Ming Gao; Chuanfu Wu; Shuang Li; Yu-you Li; Qunhui Wang (Environmental Research, 2024)

Electricity-carbon coupling retail package optimization considering low-carbon benefits of distributed renewable energy - Hongjun Gao; Qianzhen Chen; Shuaijia He; Zhiyuan Tang; Haibo Li; Junyong Liu (Journal of Cleaner Production, 2024)

Pathogenicity and horizontal transmission evaluation of a novel isolated African swine fever virus strain with a three-large-fragment-gene deletion - Han Gao; Dongdong Di; Qianwen Wu; Jie Li; Xing Liu; Zhiying Xu; Sijia Xu; Chengyu Wu; Lang Gong; Yankuo Sun; Guihong Zhang; Hongjun Chen; et al. (Veterinary Microbiology, 2024)

Long-term Fertilizer Application Induces Changes in Carbon Storage and Distribution, and the Consequent Color of Black soil - Jichao Gao; Lichun Wang; Jiafa Luo; Hongjun Gao; Weiwen Qiu; Qiang Li; Xiuzhi Zhang; Ping Zhu; Chang Peng; Yunfei Jiao; Lingying Xu (Journal of Soil Science and Plant Nutrition, 2024)

Enhanced management and antifouling performance of a novel NiFe-LDH@MnO2/PVDF hybrid membrane for efficient oily wastewater treatment - Kai Fan; Ning Kong; Jing Ma; Hongjun Lin; Chuanyang Gao; Jinshen Lei; Zihang Zeng; Jun Hu; Juncheng Qi; Liguo Shen (Journal of Environmental Management, 2024)

Assembly mechanisms of microbial communities in plastisphere related to species taxonomic types and habitat niches - Yi Sun; Hongjun Li; Jinyong Zhang; Haining Wang; Xiaoyu Cui; Xin Gao; Wenwen Qiao; Yuyi Yang (Marine Pollution Bulletin, 2024)

Soil organic carbon priming co-regulated by labile carbon input level and long-term fertilization history - Lei Wu; Jun Wang; Hu Xu; Xinliang Xu; Hongjun Gao; Minggang Xu; Wenju Zhang (Science of The Total Environment, 2023)

Zero-carbon-driven multi-energy coordinated sharing model for building cluster - Hongjun Gao; Leilei Wang; Shuaijia He; Junyong Liu (Journal of Cleaner Production, 2023)

The Effect of Crop Residue Management and Nitrogen Supply on Canopy Light Interception and N Distribution - Xiangzeng Meng; Shan Zhang; Yongjun Wang; Lichun Wang; Hongjun Gao; Yanjie Lv (International Journal of Plant Production, 2023)

Vortex-induced vibration and hydrodynamic characteristics of a round-ended cylinder - Hongjun Zhu; Bing Xu; Md Mahbub Alam; Yue Gao; Tongming Zhou (Ocean Engineering, 2023)

Green electricity trading driven low-carbon sharing for interconnected microgrids - Hongjun Gao; Mingyang Hu; Shuaijia He; Junyong Liu (Journal of Cleaner Production, 2023)

Multi-walled carbon nanotube induced liver injuries possibly by promoting endoplasmic reticulum stress in Cyprinus carpio - Xiaochan Gao; Chaoran Ma; Hongjun Wang; Chunnuan Zhang; Yong Huang (Chemosphere, 2023)

Physically separated soil organic matter pools as indicators of carbon and nitrogen change under long-term fertilization in a Chinese Mollisol - Adnan Mustafa; Qudsia Saeed; Mohammad Tahsin Karimi Nezhad; Sun Nan; Gao Hongjun; Zhu Ping; Muhammad Naveed; Xu Minggang; Avelino Nú nez-Delgado (Environmental Research, 2023)

Stock Assessment of Hatchery-Released Clam Meretrix meretrix in an Estuary of China From the Perspectives of Population Ecology and Genetic Diversity - Anguo Zhang; Hongjun Li; Xiaolong Yang; Lili Wang; Yangchun Gao; Mingshan Song; Xiutang Yuan (Frontiers in Marine Science, 2021)
In this study, the release effects of the buried clam Meretrix meretrix in a northern estuary of China (Shuangtaizi Estuary) was assessed in terms of population ecology and genetic variability by using longer-term monitoring data from 2011 (used as the baseline data) to 2018. A total of 2.4 × 10 8 hatchery juveniles were released from 2012 to 2014, and follow-up monitoring survey of the growth, distribution, density, and biomass of M. meretrix population was carried out. Results showed a temporary spike in the population of M. meretrix , and the population underwent considerable year-to-year fluctuations in total abundance and biomass. Meanwhile, the age structure of the populations from 2011 to 2018 is still an unstable expanding type. Genetic analysis based on 10 polymorphic microsatellite markers revealed no significant genetic differentiation and weak genetic structures between years but higher genetic diversities in 2014–2018 than in the initial period (2013) of stock restoration. Our study suggests that effective policies for management and conservation to restore M. meretrix population by local governments are still needed in the long run.

Potential N mineralization and availability to maize in black soils in response to soil fertility improvement in Northeast China - HaiMei Fu; YingHua Duan; Ping Zhu; HongJun Gao; MingGang Xu; XiaoMei Yang (Journal of Soils and Sediments, 2021)

Geochemistry and Petrogenesis of Volcanic Rocks from the Continent-Ocean Transition Zone in Northern South China Sea and Their Tectonic Implications - Yue Xu; Yaoming Yang; Hongjun Yu; Wei Gao; Xiangxing Gao; Baohua Liu; Xu Tian; Jichao Yang; Wenquan Zhang (Journal of Ocean University of China, 2020)

Salvianolic acid A attenuated myocardial infarction–induced apoptosis and inflammation by activating Trx - Rui Zhou; Jinhuan Gao; Changpei Xiang; Zhenming Liu; Yi Zhang; Jingjing Zhang; Hongjun Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Phytoplankton pigment pattern in the subsurface chlorophyll maximum in the South Java coastal upwelling system, Indonesia - Chunlei Gao; Mingzhu Fu; Hongjun Song; Lei Wang; Qinsheng Wei; Ping Sun; Lin Liu; Xuelei Zhang (Acta Oceanologica Sinica, 2018)

Breeding potential of maize germplasm populations to improve yield and predominant heterotic pattern in Northeast China - Hongjun Yong; Zhenguo Jin; Li Gao; Lin Zhang; Xianjun Liu; Fangjun Zhang; Xiaocong Zhang; Degui Zhang; Mingshun Li; Jianfeng Weng; Zhuanfang Hao; Shihuang Zhang; et al. (Euphytica, 2017)

Efficacy and safety of quetiapine extended release monotherapy in bipolar depression: a multi-center, randomized, double-blind, placebo-controlled trial - Huafang Li; Niufan Gu; Hongyan Zhang; Gang Wang; Qingrong Tan; Fude Yang; Yuping Ning; Honggeng Zhang; Zheng Lu; Xiufeng Xu; Jianguo Shi; Chengge Gao; et al. (Psychopharmacology, 2016)

Identification and validation of novel low-tiller number QTL in common wheat - Zhiqiang Wang; Yaxi Liu; Haoran Shi; Hongjun Mo; Fangkun Wu; Yu Lin; Shang Gao; Jirui Wang; Yuming Wei; Chunji Liu; Youliang Zheng (Theoretical and Applied Genetics, 2016)

Development and characterization of 13 polymorphic microsatellite markers for the Chinese surf clam (Mactra chinensis) through Illumina paired-end sequencing - Hongjun Li; Jingjing Zhang; Hongbo Li; Xianggang Gao; Chongbo He (Conservation Genetics Resources, 2014)

Characterization of 10 polymorphic microsatellite markers for Mediterranean blue mussel Mytilus galloprovincialis by EST database mining and cross-species amplification - HONGJUN LI; YU LIANG; LIJUN SUI; XIANGGANG GAO; CHONGBO HE (Journal of Genetics, 2013)

The Alteration of MiR-222 and Its Target Genes in Nickel-Induced Tumor - Jing Zhang; Yang Zhou; Lin Ma; Shunquan Huang; Ruijin Wang; Rongrong Gao; Youjun Wu; Hongjun Shi; Jun Zhang (Biological Trace Element Research, 2013)

Intracellular Cu/Zn superoxide dismutase (Cu/Zn-SOD) from hard clam Meretrix meretrix: its cDNA cloning, mRNA expression and enzyme activity - Xianggang Gao; Chongbo He; Hong Liu; Hongjun Li; Dan Zhu; Shengli Cai; Ying Xia; Ying Wang; Zhe Yu (Molecular Biology Reports, 2012)

Membrane Bioreactors for Industrial Wastewater Treatment: A Critical Review - Hongjun Lin; Weijue Gao; Fangang Meng; Bao-Qiang Liao; Kam-Tin Leung; Leihong Zhao; Jianrong Chen; Huachang Hong (Critical Reviews in Environmental Science and Technology, 2012)

Molecular analysis and recombinant expression of bovine neutrophil β-defensin 12 and its antimicrobial activity - Jianming Wu; Changfa Wang; Hongbin He; Guixue Hu; Hongjun Yang; Yundong Gao; Jifeng Zhong (Molecular Biology Reports, 2011)

Mining single nucleotide polymorphisms from EST data of hard clam Meretrix meretrix - Hongjun Li; Dan Zhu; Xianggang Gao; Yun-feng Li; Jian Wang; Chongbo He (Conservation Genetics Resources, 2010)